Peranan Subsektor Holtikultura, Kontribusi Pembagunan Wilayah Di Kabupaten Halmahera Selatan: Kabupaten Halmahera Selatan - muhammad, musdar; Nasar, Fahima; Kamal, Muhammad; Hadi, Aswir; Khotib, Muhammad; Amana, Asbur (Jurnal Bingkai Ekonomi (JBE), 2024)
The purpose of the study; To find out the Horticultural Commodities and how the components of growth in the agricultural sub-sector what is the base sector. the method used is descriptive kuntitaf by using analytical tools Quotient Analysis (LQ) and Shift Share Analysis (SSA). The results showed that; Horticulture subsector on vegetable commodities that have a base sector (LQ = 1) there are vegetables; ketimum, kale, long kancang, spinach, cayenne pepper, red pepper, and LQ>1 is the commodity shallots, while for commodities fruits base sector (LQ = 1) there are only three fruits, namely papaya, jackfruit and mango fruit, and LQ>1 on fruits is found on bananas. Horticulture Subsector of Fruits and Vegetables Proportional Growth Component (Proportional Shift) of South Halmahera Regency has a very good economic growth for the long term in South Halmahera Regency